Prevention Practice of COVID-19 Using Personal Protective Equipment and Hand Hygiene Among Healthcare Workers in Public Hospitals of South Wollo Zone, Ethiopia - Keleb, Awoke; Ademas, Ayechew; Lingerew, Mistir; Sisay, Tadesse; Berihun, Gete; Adane, Metadel (Frontiers in Public Health, 2021)
Objective: Use of personal protective equipment and hand hygiene are often the cost effective line of defense against Corona Virus Disease-19 (COVID-19) pandemic. The purpose of this study is to determine the magnitude of compliance and associated factors of personal protective equipment utilization and hand hygiene practice among health care workers in public hospitals of South Wollo Zone, Northeastern Ethiopia. Methods: Hospital-based cross-sectional study was conducted among 489 healthcare workers in public hospitals of South Wollo Zone, Northeastern Ethiopia from June to July, 2021. Proportional sample size allocation to each selected hospitals followed by simple random sampling techniques was used to select the study participants using human resource records from each hospital. A pre-tested and structured self-administered questionnaire was used to collect data. Bivariate and multivariable analyses with 95% CI and p- value <0.05 were employed to identify the associated effect of each explanatory variable on dependent variable. Results: About 32% and 22.3% of healthcare workers were compliant with personal protective equipment utilization and hand hygiene practice respectively. Feedback for safety (AOR=2.05; 95% CI: 1.26-3.35), training on COVID-19 prevention (AOR=3.43; 95% CI: 2.01-5.86) and perception to infection risk (AOR=1.98; 95% CI: 1.18-3.33) were significant factors of compliance with personal protective equipment utilization Conclusion: This study showed that the magnitude of compliance with personal protective equipment utilization and hand hygiene was low. Interventions to promote personal protective equipment utilization and hand hygiene should focus on feedback for safety, training on COVID-19 prevention and perception to infection risk.